Knowledge of Health Care Providers of a Tertiary Hospital Regarding Post-Operative Infection (Journal of Preventive and Social Medicine, 2022)
Background: Infection is a very common post-operative complication. Now a day the knowledge about infection among healthcare provider is very essential. The study was aimed to determine the knowledge health care provider regarding the management of infection in postoperative ward.Methods: The cross-sectional study was conducted among 90 respondents (60 doctors, 50 nurses & 40 supporting staff) from January 2015 to December 2015 in Dhaka Medical College and Hospital. A semi structured questionnaire was used to obtain socio-demographic data and infection management related information from the respondents through face to face interview. In-depth interviews were taken from director of DMCH, head of the department of surgery and nurse in-charge in post-operative ward for qualitative data. After collection data were complied, summarized and analyzed. The study was approved by ethical committee of National institute of Preventive and Social Medicine. Before collection of data, written permission was taken from the director of the selected hospital & take consent from the respondents.Results: Among 150 respondents, 58% were female with 26-30 years age group. Most doctors were post-graduate & nurses were diploma in nursing. Most of doctors had knowledge about infections- 83.3% told bacterial as a type, 80% told devices as a source and 94% told diabetes as a risk factor. Both doctors and nurses had knowledge about the causes and mode of transmission of infection (90% doctors & 93.2% nurses told unsterile instrument), complication due to infection (100% doctors told sepsis & 86.7% nurses told wound become red & swelling), prevention (100% doctors &92% nurses told proper sterilization of instrument). Doctors (95% and nurse (74%) known about infection control guideline and. Doctors (47.5%) and nurses (68%) received training about infection management Among 40 staff 80% were known about infection and they knew from their colleague. 82.5% staffs known about sterilization.Conclusion: This finding had great impact for management of infection and it will be beneficial for all HCW to receive formal and periodic refresher trainings.JOPSOM 2021; 40(1): 43-50